Directions of Changes in Customs Control - Laszuk, Mirosława (Journal of Finance and Financial Law, 2024)
The purpose of the article. In the article, two objectives are indicated: the first – the indication of the specific features of customs control as well as the identification and evaluation of the most important changes within this process with consideration for the specific conditions caused by the incompatibilities between the paradigm of facilitating and simplifying the international trade in goods and that of its security. Achieving the above purposes will allow for verification of the hypothesis that the fiscal purpose of customs control has been significantly diminished in favor of security. Methodology. The methodology of the article is based on the analysis of subject-related literature, and document study. The article also uses a statistical method. Results of the research. Implementing facilitation and enhancing security in the international trade has brought significant changes in customs control. The importance of risk management has increased, and the institution of the authorized economic operator has been introduced. Complicated structures of global supply chains, new forms of criminal activity and the war in Ukraine confirm that it is primarily security that should be the goal of customs control. However, this results in a reduced importance of the fiscal objective.